CIVIC IDENTITY AND POLITICAL VALUES OF THE YOUTH OF RUSSIA - S. U. Ivanova (Гуманитарные и юридические исследования)
The article discusses the political values of modern Russian youth, their dynamics and specifics in relation to the North Caucasus region. Analyzes the causes of ethnicising politics and politicization of ethnicity. The necessity of strengthening of political nation in Russia and the displacement of ethnic markers from the field of political-ski in the area of culture.